Oligodendrocyte Precursor Cells Modulate the Neuronal Network by Activity-Dependent Ectodomain Cleavage of Glial NG2 - Sakry, Dominik; Neitz, Angela; Singh, Jeet; Frischknecht, Renato; Marongiu, Daniele; Biname, Fabien; Perera, Sumudhu S.; Endres, Kristina; Lutz, Beat; Radyushkin, Konstantin; Trotter, Jacqueline; Mittmann, Thomas (Plos Biology, 2014)
The role of glia in modulating neuronal network activity is an important question. Oligodendrocyte precursor cells (OPC) characteristically express the transmembrane proteoglycan nerve-glia antigen 2 (NG2) and are unique glial cells receiving synaptic input from neurons. The development of NG2+ OPC into myelinating oligodendrocytes has been well studied, yet the retention of a large population of synapse-bearing OPC in the adult brain poses the question as to additional functional roles of OPC in the neuronal network. Here we report that activity-dependent processing of NG2 by OPC-expressed secretases functionally regulates the neuronal network. NG2 cleavage by the α-secretase ADAM10 yields an ectodomain present in the extracellular matrix and a C-terminal fragment that is subsequently further processed by the γ-secretase to release an intracellular domain. ADAM10-dependent NG2 ectodomain cleavage and release (shedding) in acute brain slices or isolated OPC is increased by distinct activity-increasing stimuli. Lack of NG2 expression in OPC (NG2-knockout mice), or pharmacological inhibition of NG2 ectodomain shedding in wild-type OPC, results in a striking reduction of N-methyl-D-aspartate (NMDA) receptor-dependent long-term potentiation (LTP) in pyramidal neurons of the somatosensory cortex and alterations in the subunit composition of their α-amino-3-hydroxy-5-methyl-4-isoxazolepr opionicacid (AMPA) receptors. In NG2-knockout mice these neurons exhibit diminished AMPA and NMDA receptor-dependent current amplitudes; strikingly AMPA receptor currents can be rescued by application of conserved LNS protein domains of the NG2 ectodomain. Furthermore, NG2-knockout mice exhibit altered behavior in tests measuring sensorimotor function. These results demonstrate for the first time a bidirectional cross-talk between OPC and the surrounding neuronal network and demonstrate a novel physiological role for OPC in regulating information processing at neuronal synapses.
CRIS-Team Scopus Importer:2022-08-05